Human Milk Fatty Acid Composition and Its Effect on Preterm Infants' Growth Velocity - Batool Ahmed; Afnan Freije; Amina Omran; Mariangela Rondanelli; Mirko Marino; Simone Perna (MDPI AG, 2023)
This study aimed to analyze the fatty acid content in human milk and to find its relationship with the growth velocity of preterm infants. Mature milk samples from 15 mothers of preterm infants were collected from three different hospitals, followed by lipid extraction, fatty acid methylation, and finally gas chromatography analysis to determine the fatty acids composition. The average total lipid content was 3.61 ± 1.57 g/100 mL with the following classes of fatty acids: saturated fatty acids 43.54 ± 11.16%, unsaturated fatty acids 52.22 ± 10.89%, in which monounsaturated fatty acids were 36.52 ± 13.90%, and polyunsaturated fatty acids were 15.70 ± 7.10%. Polyunsaturated fatty acid sub-class n-6 was 15.23 ± 8.23% and n-3 was 0.46 ± 0.18%. Oleic acid, palmitic acid, and linoleic acid were the most abundant fatty acids. The n-6/n-3 ratio was 32.83:1. EPA and DHA fatty acids were not detected. As gestational age and birth weight increase, C20:2n6 content increases. The growth velocity increases with the decrement in C16 and increment in C20:2n6. The lipid profile of preterm human milk was found to be low in some essential fatty acids, which may affect the quality of preterm infants' nutrition.